A multi-criteria decision-making framework for the location of photovoltaic power coupling hydrogen storage projects. (15th December 2021) - Gao, Jianwei; Men, Huijuan; Guo, Fengjia; Liang, Pengcheng; Fan, Yuejin
Highlights: Construct a criteria system for PVPCHS projects. Define the recognition degree formula of PLTS. Define the real preference formula of PLTS, and extend the method of TODIM. Defines the Tversky similarity of PLTS, and establish the weight model of DMs through social network diagrams. Establish the criteria weight model based on the maximization of distance deviation. Abstract: In order to adapt new energy sources to the grid and improve the reliability and safety of grid power supply, photovoltaic power coupling hydrogen storage (PVPCHS) projects have been extensively developed. Site selection is a multi-criteria decision-making (MCDM) problem. Thus, this paper proposes a MCDM framework for the location of PVPCHS projects. First of all, this paper constructs an index system for PVPCHS projects including four criteria and sixteen sub-criteria. Secondly, this paper defines the recognition degree formula of PLTS fully considering the uncertainty of decision-makers (DMs) and avoiding the loss of decision information. Thirdly, this paper defines the real preference formula of PLTS by introducing the idea of orness measurement, then extended the method of TODIM (TOmada de Decisao Iterativa Multicriterio). Fourthly, DMs' weight model is established through social network diagrams. At the same time, criteria weight model is established based on the maximization of distance deviation. Furthermore, a MCDM framework is proposed. Finally, through a case in Inner Mongolia of China to prove the effectiveness and superiority of the proposed MCDM method. The results proves that Hohhot in Inner Mongolia is the optimal location for PVPCHS projects. This work provides a scientific method for the location of PVPCHS projects.